Analisis Budaya Organisasi Menggunakan Organizational Culture Assessment Instrument (OCAI) pada Karyawan PT Eddy Transport Raya - Teguh Widodo; Sufarddin Bin Hasaruddin; Nur Wening (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2022)
This study aims to describe the current and preferred organizational culture profile of PT Eddy Transport Raya based on the perceptions of all employees. The sampling method in this study is included in the type of saturated sample, where all the population numbers are samples. The total population in this study was 33 consisting of all employees of PT Eddy Transport Raya, so there were 33 people to be used as samples for research data collection. Primary data collection was carried out by distributing OCAI (Organizational Culture Assessment Instrument) questionnaires to all employees. The variable in this study is organizational culture with 4 indicators indicator or type of culture namely Clan, Adhocracy, Market and Hierarchy. The results of these 4 indicators provide an understanding of the organizational culture of the company. Thus it can help leaders in terms of communication and decision making within the company. In this study, employees have the perception that the current organizational culture of PT Eddy Transport Raya is more towards clan culture. In addition, employees have the desire to change and improve the organizational culture to become adhocracy.